FAKTOR RISIKO KEJADIAN BERAT BADAN LAHIR RENDAH PADA MASYARAKAT PENAMBANG BATU DI WILAYAH MORAMO UTARA : Risk Factors for Low Birth Weight in The Community of Stone Miners in The North Moramo Region - Liyusri; Tasnim; Sultan Akbar Toruntju (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Cases of low birth weight (LBW) are at risk of increasing mortality and morbidity, it is necessary to identify identification of LBW incidence factors. This study analyzed the risk factors for LBW events. This research is a study consisting of two groups and case control designed with a case study design. The population is mothers who have been collected with a sample of 54 respondents divided into two case groups and a control group. Sampling in the study group with a simple random sampling technique and in the control group took samples that matched the age group so that they obtained the same number of samples between the case group and the control group. Variables published were age at pregnancy, parity, diet and disease history, analysis of data using Odd Ratio and multivariate logistic regression (a = 0.05).Factors associated with low birth weight during pregnancy were age (p = 0.013), parity (p = 0.002), diet (p = 0.001) and disease history (p = 0.000). The results of logistic regression analysis showed that the age during pregnancy was a risk factor for LBW and the most influential factor (OR = 13,311; 95% CI 1,753-101,080). age (<20 and> 35 years) has a risk of 13 times giving birth to babies with low births compared to mothers aged 20-35 years. It is expected that the mother avoids the risk of pregnancy at age (<20 years and> 35 years) and the dissemination of related health workers about risky pregnancies to reduce the risk of LBW. Keywords : Age; parity;diet; history of disease; LBW.